The Phenomena of Plagiarism in Hindu Perspective - I Dewa Gede Rat Dwiyana Putra (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2017)
This article was made based on an observation on the thesis written by undergraduate student. The basic reason for the application of this research is that, there were many problem found in the students writing especially the in the citation process and referencing technique which would bring them to commit plagiarism. Since writing a thesis is essential for the undergraduate students to finish their study, this research would be very beneficial evidence to give a clear picture about plagiarism from Hindus teaching perspective. Library research is the primary method applied in conducting this research. The result shows that there are typical mistakes done by the students in doing citation and referencing. Then, suggestions to those problems were given based on Hindus perspective.